Forming method of nanocrystalline special-shaped thin-wall part and nanocrystalline special-shaped thin-wall part
By using a polymer prepolymer mixed with a metal ion solution to generate a uniform distribution of nano- and micro-conductive particles in the forming method of nanocrystalline irregular thin-walled parts, and combining soft etching and micro-electroforming technologies, the problems of high forming accuracy and cost in traditional methods are solved, achieving efficient and precise forming and low-cost production.
Patent Information
- Application Number
- CN202411646980.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional forming methods are difficult to guarantee the forming accuracy and shape accuracy of nanocrystalline irregular thin-walled parts, and the high manufacturing cost and long forming cycle limit their application in large-scale production.
A uniform distribution of nano-conductive particles and external micron-conductive particles is generated by mixing polymer prepolymer with metal ion solution. Combined with soft etching and micro-electroforming technology, nanocrystalline irregular thin-walled parts are prepared by electrodeposition. An elastic polymer core mold is used to reduce demolding damage and lower the core mold preparation cost.
It improves the forming accuracy and service performance of nanocrystalline irregular thin-walled parts, reduces manufacturing costs and forming cycle, and meets the needs of large-scale production.
Smart Images

Figure CN119392322A_ABST
Abstract
Description
Technical Field
[0001] The disclosed embodiments relate to the field of precision forming technology, and in particular, to a forming method of a nanocrystalline special-shaped thin-walled part and a nanocrystalline special-shaped thin-walled part. Background Art
[0002] With the rapid development of science and technology, nanocrystalline materials have shown broad application prospects in many fields such as electronics, optics, and catalysis due to their unique physical and chemical properties. As a component with a special shape and thin-walled structure, special-shaped thin-walled parts also have vital applications in high-end fields such as national defense, military industry, precision transmission, and new energy. However, the traditional forming method has the following problems when preparing nanocrystalline special-shaped thin-walled parts: the traditional forming process is difficult to ensure the forming accuracy. Due to the special properties of nanocrystalline materials and the complex structure of special-shaped thin-walled parts, traditional machining is difficult to accurately control the distribution and organizational structure of the material, resulting in the dimensional accuracy and shape accuracy of the formed parts being difficult to meet actual needs. Traditional machining preparation costs are high and the forming cycle is long. This not only increases the production cost of the product, but also seriously affects the production efficiency, limiting its application in large-scale production.
[0003] Although the new micro-electroforming technology developed with the help of electricity has solved the problems of traditional machining to a certain extent, its widespread application still faces many challenges. For example, the existing micro-electroforming core molds are mainly formed by photolithography, which leads to high preparation costs and short service life. Summary of the invention
[0004] The purpose of the present disclosure is to provide a forming method of nanocrystalline shaped thin-walled parts and nanocrystalline shaped thin-walled parts, thereby at least to a certain extent overcoming the problems of high production cost and low precision of nanocrystalline shaped thin-walled parts caused by the limitations and defects of related technologies.
[0005] According to one aspect of the present disclosure, a method for forming a nanocrystalline shaped thin-walled part is provided, comprising: mixing a polymer prepolymer with a metal ion solution, allowing the metal ions to generate nano conductive particles in situ in the polymer prepolymer through a liquid phase reaction, adding micron conductive particles to the polymer prepolymer containing the nano conductive particles, and dispersing them uniformly by ultrasonication to obtain a polymer conductive slurry; adding a curing agent to the polymer conductive slurry, stirring it uniformly and pouring it onto the surface of an original template, demolding it after curing and forming, and obtaining a polymer core mold with an original template structure; immersing the polymer core mold as a cathode in an electroforming liquid, reducing the metal ions in the electroforming liquid to metal atoms through electrodeposition, and depositing them in a core mold cavity until the core mold cavity is filled; demolding the nanocrystalline shaped thin-walled part from the core mold cavity to obtain a nanocrystalline shaped thin-walled part.
[0006] In an exemplary embodiment of the present disclosure, the polymer prepolymer is polydimethylsiloxane or epoxy resin.
[0007] In an exemplary embodiment of the present disclosure, the weight ratio of the metal ion solution to the polymer prepolymer is 2 to 3:1.
[0008] In an exemplary embodiment of the present disclosure, the micron conductive particles are metal powder or carbon-based conductive material, the metal powder is silver powder, copper powder or nickel powder, and the carbon-based conductive material is graphene, carbon nanotubes or graphite.
[0009] In an exemplary embodiment of the present disclosure, the weight ratio of the micron conductive particles to the polymer prepolymer is 2 to 5:1.
[0010] In an exemplary embodiment of the present disclosure, the weight ratio of the polymer conductive paste to the curing agent is 1 to 10:1.
[0011] In an exemplary embodiment of the present disclosure, the process parameters of the electrodeposition include one or more of current density, temperature and time, and the current density is 1 to 20 A / dm 2 The temperature is 30-80° C., and the time is determined according to the thickness of the nanocrystalline special-shaped thin-walled part.
[0012] In an exemplary embodiment of the present disclosure, the electroforming liquid is a single metal electroforming liquid, an alloy electroforming liquid or a composite electroforming liquid.
[0013] In an exemplary embodiment of the present disclosure, after demolding the nanocrystalline shaped thin-walled part from the core mold cavity, the method further includes: post-processing the removed nanocrystalline shaped thin-walled part, wherein the post-processing includes one or more of ultrasonic cleaning, heat treatment and surface polishing.
[0014] According to one aspect of the present disclosure, a nanocrystalline shaped thin-walled part is provided. The nanocrystalline shaped thin-walled part is prepared according to any one of the above-mentioned forming methods of the nanocrystalline shaped thin-walled part.
[0015] In the technical solution provided in the embodiments of the present disclosure, on the one hand, the uniform distribution of in-situ nano-conductive particles and externally added micron-conductive particles generated by mixing a polymer prepolymer with a metal ion solution can improve the uniformity of the distribution of electric lines during the electroforming process, improve the conductivity of the polymer conductive slurry, and help improve the forming accuracy. Soft etching can accurately replicate the shape of the original template, and the elastic polymer core mold can reduce the damage to the microstructure during the demolding process, thereby improving the forming accuracy. On the other hand, the elastic polymer core mold can release residual stress during the deposition process, avoid deformation and defects caused by stress concentration, and improve the service performance of the prepared nanocrystalline special-shaped thin-walled parts. On the other hand, the core mold is prepared by soft etching technology, and the traditional high-cost conductive materials are partially replaced by in-situ self-generation and externally added conductive particles. Expensive photolithography equipment and complex processes are not required, which reduces the cost of core mold preparation, shortens the forming cycle, and improves production efficiency. It can meet large-scale production applications and further improve the service life of the core mold. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0017] Figure 1 A flow chart schematically shows a method for forming a nanocrystalline special-shaped thin-walled part in an embodiment of the present disclosure.
[0018] Figure 2 Schematic diagram of the microscopic morphology of the nanocrystalline special-shaped thin-walled part prepared according to Example 1.
[0019] Figure 3 Schematic diagram of the microscopic morphology of the nanocrystalline special-shaped thin-walled parts prepared according to Example 2.
[0020] Figure 4 Schematic diagram of the microscopic morphology of the nanocrystalline special-shaped thin-walled parts prepared according to Example 3. DETAILED DESCRIPTION
[0021] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0022] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.
[0023] As a component with a special shape and thin-walled structure, special-shaped thin-walled parts also have vital applications in high-end fields such as national defense, military industry, precision transmission and new energy. However, the traditional forming method has the following problems when preparing nanocrystalline special-shaped thin-walled parts: the traditional forming process is difficult to ensure the forming accuracy. Due to the special properties of nanocrystalline materials and the complex structure of special-shaped thin-walled parts, traditional machining is difficult to accurately control the distribution and organizational structure of the material, resulting in the size accuracy and shape accuracy of the formed parts being difficult to meet actual needs. Traditional machining preparation costs are high and the forming cycle is long. This not only increases the production cost of the product, but also seriously affects the production efficiency, limiting its application in large-scale production.
[0024] Although the micro-electroforming technology developed with the help of electric energy has solved the above problems to a certain extent, the preparation of micro-electroforming core molds still faces many challenges. For example, the existing micro-electroforming core molds are mainly formed by photolithography technology, resulting in high preparation costs and short service life. These problems seriously restrict the widespread application of micro-electroforming technology in the preparation of nanocrystalline special-shaped thin-walled parts.
[0025] Based on this, the present disclosure provides a method for forming a nanocrystalline shaped thin-walled part in an embodiment, which is used to prepare a nanocrystalline shaped thin-walled part. Figure 1As shown in , it is intended to provide a method for realizing precision forming of nanocrystalline special-shaped thin-walled parts by soft etching combined with micro-electroforming, reduce the core mold preparation cost and forming cycle, and improve the forming accuracy and service performance of the product. The method mainly includes the following steps:
[0026] In step S110, a polymer prepolymer is mixed with a metal ion solution, and the metal ions are used to generate nano-conductive particles in the polymer prepolymer in situ through a liquid phase reaction, and micron-conductive particles are added to the polymer prepolymer matrix containing the nano-conductive particles, and ultrasonic dispersion is used to uniformly disperse the nano-conductive particles to obtain a polymer conductive slurry;
[0027] In step S120, a curing agent is added to the polymer conductive paste, stirred evenly, and then poured onto the surface of the original template, and demolded after curing and forming to obtain a polymer core mold with the original template structure;
[0028] In step S130, the polymer core mold is immersed in the electroforming liquid as a cathode, and the metal ions in the electroforming liquid are reduced to metal atoms by electrodeposition, and deposited in the core mold cavity until the core mold cavity is filled;
[0029] In step S140, the nanocrystalline special-shaped thin-walled part is demolded from the core mold cavity to obtain the nanocrystalline special-shaped thin-walled part.
[0030] Next, the forming method of the nanocrystalline special-shaped thin-walled part in the embodiment of the present disclosure is specifically described.
[0031] In the embodiments of the present disclosure, a method for precision forming of nanocrystalline special-shaped thin-walled parts is proposed, which aims to improve the forming accuracy of nanocrystalline special-shaped thin-walled parts, reduce the preparation cost, shorten the forming cycle, and improve the forming accuracy and service performance of the products, thereby promoting the widespread application of nanocrystalline materials and special-shaped thin-walled parts in various fields.
[0032] In step S110, the polymer prepolymer is mixed with the metal ion solution, and the metal ions are used to generate nano conductive particles in situ in the polymer prepolymer through a liquid phase reaction. Micro conductive particles are added to the polymer prepolymer matrix containing the nano conductive particles and dispersed evenly by ultrasonication to obtain a polymer conductive slurry.
[0033] In the disclosed embodiment, the polymer prepolymer may be polydimethylsiloxane or epoxy resin. The metal ion solution refers to a solution containing metal ions. The metal ion solution may be one of a chemical copper plating solution, a chemical silver plating solution, and a chemical nickel plating solution, which is specifically determined according to the type of the polymer prepolymer. Wherein, without limiting the type of metal ions, the weight ratio of the metal ion solution to the polymer prepolymer is 2 to 3:1.
[0034] The polymer prepolymer is mixed with the metal ion solution, and the metal ions are used to generate nano-conductive particles in situ in the polymer prepolymer through liquid phase reaction, and micron conductive particles are added to the polymer prepolymer containing nano-conductive particles. The time and temperature of the liquid phase reaction may vary according to the solution. The added micron conductive particles may be metal powder or carbon-based conductive materials, the metal powder may be any one of silver powder, copper powder or nickel powder, and the carbon-based conductive material may be any one of graphene, carbon nanotubes or graphite. The particle size of the added micron conductive particles may be any suitable particle size, which is determined according to actual needs. For example, the particle size of the added micron conductive particles may be 1 μm, 5 μm, 10 μm, 150 μm, etc. The weight ratio of the micron conductive particles to the polymer prepolymer is 2 to 5:1.
[0035] In some embodiments, a polymer prepolymer can be used as a matrix, and nano-conductive particles can be generated in situ of the polymer prepolymer through a liquid phase reaction. Adding micron-conductive particles to the matrix containing the nano-conductive particles can act as a bridge between the micron-conductive particles in the gaps and fill the gaps. The coupling effect between the in-situ generated nano-conductive particles and the added micron-conductive particles can increase the conductivity.
[0036] Furthermore, after adding micron conductive particles to the polymer prepolymer matrix containing nano conductive particles, ultrasonic dispersion can be used to obtain polymer conductive slurry. Ultrasonic dispersion can be ultrasonic dispersion in an ultrasonic cleaner, and the time for ultrasonic dispersion can be determined according to actual needs. The conductivity of the polymer conductive slurry is improved by matching the micron conductive particles with the nano conductive particles.
[0037] In step S120, a curing agent is added to the polymer conductive paste, stirred evenly and then poured onto the surface of the original template, and demolded after being cured and formed to obtain a polymer core mold with the original template structure.
[0038] In the disclosed embodiment, the curing agent may be a curing agent that matches the polymer prepolymer, and the curing agent may be specifically determined according to the polymer prepolymer. The weight ratio of the polymer conductive paste to the curing agent may be 1 to 10:1. The original template may be any type of template, specifically determined according to the type of thin-walled part to be prepared, for example, the original template may be a stainless steel mold with a medicine cap cavity, a silicon template with a micro gear shape, or a stainless steel template surface with a grid line pattern.
[0039] The curing temperature can be room temperature, 100°C or 120°C. The curing time varies with the curing temperature. For example, when the temperature is room temperature, the curing time can be 24 hours; when the curing temperature is 100°C, the curing time can be 60 minutes; when the curing temperature is 120°C, the curing time can be 30 minutes. The curing temperature and time can be determined according to actual needs, as long as demolding can be guaranteed.
[0040] In step S130, the polymer core mold is immersed in the electroforming liquid as a cathode, and the metal ions in the electroforming liquid are reduced to metal atoms by electrodeposition, and deposited in the core mold cavity until the core mold cavity is filled.
[0041] In the embodiment of the present disclosure, the electroforming liquid can be a single metal electroforming liquid, an alloy electroforming liquid or a composite electroforming liquid. The process parameters of the electrodeposition include one or more of current density, temperature and time, wherein the current density can be 1 to 20 A / dm 2 The temperature may be 30 to 80° C., and the electrodeposition time may be determined according to the thickness of the nanocrystalline shaped thin-walled part. For example, the electrodeposition time may be positively correlated with the thickness of the nanocrystalline shaped thin-walled part. The thicker the nanocrystalline shaped thin-walled part, the longer the electrodeposition time.
[0042] After obtaining the polymer core mold, the polymer core mold can be immersed in the configured electroforming liquid as a cathode, and the metal ions in the electroforming liquid are reduced to metal atoms by electroplating, and deposited in the core mold cavity until the core mold cavity is full, and then the electroplating is stopped. The polymer core mold can be an elastic polymer core mold. The elastic polymer core mold can release residual stress during the electroplating process, avoid deformation and defects caused by stress concentration, and improve the service performance of the product.
[0043] The electrodeposition method can be direct current electrodeposition or pulse electrodeposition, which is determined according to actual needs.
[0044] In step S140, the nanocrystalline special-shaped thin-walled part is demolded from the core mold cavity to obtain the nanocrystalline special-shaped thin-walled part.
[0045] In the embodiment of the present disclosure, the nanocrystalline shaped thin-walled part can be taken out from the core mold cavity by manual demoulding, and the nanocrystalline shaped thin-walled part can be further post-processed to obtain the nanocrystalline shaped thin-walled part. The post-processing can include one or more of ultrasonic cleaning, heat treatment and surface polishing. The step of performing the post-processing can be obtained according to the preparation requirements of the nanocrystalline shaped thin-walled part.
[0046] It should be noted that the polymer core mold after demoulding can be ultrasonically cleaned in deionized water for reuse.
[0047] In the technical solution provided by the present disclosure, soft etching can accurately replicate the shape of the original template, and the elastic polymer core mold can reduce the damage to the microstructure during the demolding process, thereby ensuring the forming accuracy. The uniform distribution of in-situ nano-conductive particles and externally added micron-conductive particles can improve the uniformity of the distribution of electric lines during the electroforming process, which is beneficial to improving the forming accuracy. The elastic polymer core mold can release residual stress during the deposition process, avoid deformation and defects caused by stress concentration, and improve the service performance of the product. Through the core mold preparation method and micro-electroforming process, the precise forming of nanocrystalline special-shaped thin-walled parts is achieved, and the quality is improved. The core mold is prepared by soft etching technology, which does not require expensive lithography equipment and complex processes, thereby reducing the cost of core mold preparation. By using in-situ self-generation and externally added conductive particles, traditional high-cost conductive materials are partially replaced, further reducing costs and increasing the service life of the core mold.
[0048] Next, the forming method of the nanocrystalline special-shaped thin-walled part provided by the present disclosure is described in detail with reference to the embodiments.
[0049] Example 1
[0050] The nanocrystalline shaped thin-walled part prepared in this embodiment is a nanocrystalline copper liner for armor-piercing projectiles. The polymer prepolymer used is an epoxy resin prepolymer, the metal ion solution is an electroless copper plating solution, the added micron conductive particles are copper powder, the original template is a stainless steel mold with a liner cavity, and the electroforming liquid is a copper sulfate electroforming liquid.
[0051] The specific preparation process includes the following steps:
[0052] Step 1, preparation of epoxy resin conductive paste: add 500mL chemical copper plating solution to 200mL epoxy resin prepolymer and react at room temperature for 90min, generate nano copper conductive particles in situ in the epoxy resin conductive prepolymer by liquid phase reduction reaction, and then ultrasonicate for 100min in an ultrasonic cleaner so that the nano copper conductive particles are evenly dispersed in the epoxy resin prepolymer to obtain epoxy resin prepolymer containing nano copper conductive particles. Then add 500g of copper powder with a particle size of 2 to 5μm to the epoxy resin prepolymer matrix containing nano copper conductive particles, ultrasonically disperse for 300min in an ultrasonic cleaner so that the copper powder is evenly dispersed in the epoxy resin prepolymer matrix to prepare a polymer conductive paste, which is epoxy resin conductive paste. Among them, the copper powder is an added micron conductive particle.
[0053] The components of the chemical copper plating solution include: 50 g / L potassium sodium tartrate, 30 g / L copper sulfate, 3 g / L sodium borohydride, and 30 g / L sodium hydroxide. The pH value of the chemical copper plating solution is adjusted to 13.0 or other suitable values by using a dilute sulfuric acid solution to improve the solution stability.
[0054] Step 2, epoxy resin core mold soft etching forming: add 200mL of curing agent to the epoxy resin conductive paste containing the added micron copper powder, and then pour it into a stainless steel mold with a liner cavity after mechanical stirring, and then place it at room temperature for 24 hours to cure and finally demold to obtain a polymer core mold with the original template structure. The polymer core mold here can be an epoxy resin core mold with a liner structure.
[0055] Step 3: Micro-electroforming of the liner: The epoxy resin core mold is used as the cathode and immersed in the copper sulfate electroforming solution. The pure copper plate is used as the anode and the electrodeposition is carried out at 30°C. The current density used for the electrodeposition is 20A / dm 2 The electrodeposition method is direct current electrodeposition, and the electrodeposition time can be 20 hours. After the core model cavity is filled with casting, the electrodeposition is stopped to obtain the nanocrystalline copper charge liner.
[0056] The components of the copper sulfate electroplating solution include: 130 g / L copper sulfate, 150 g / L sulfuric acid, 1 g / L sodium chloride, 5 mg / L gelatin, and 5 mg / L polyethylene glycol.
[0057] Step 4, demoulding and post-processing: The nanocrystalline copper liner is removed from the core mold cavity by manual demoulding, and then cleaned with deionized water, and finally the outer surface is polished to obtain the nanocrystalline copper liner. The nanocrystalline copper liner is the nanocrystalline special-shaped thin-walled part prepared in Example 1. The epoxy resin core mold after demoulding is ultrasonically cleaned in deionized water for reuse.
[0058] Figure 2 This is a microscopic morphology of a nanocrystalline copper liner with a diameter of 80 mm prepared in Example 1. Figure 2 It can be seen that the copper liner prepared in this embodiment has a nanocrystalline structure, which can effectively improve the service performance of the sample.
[0059] Example 2
[0060] The nanocrystalline special-shaped thin-walled parts used to prepare in this embodiment are thin-walled gear parts for precision transmission. The polymer prepolymer used is polydimethylsiloxane prepolymer, and the metal ion solution is a chemical silver plating solution. The added micron conductive particles are conductive graphite powder. The original template is a silicon template with a micro-gear shape, and the electroforming liquid is a nickel / aluminum oxide composite electroforming liquid, that is, a nickel sulfate electroforming liquid containing aluminum oxide. The specific preparation process includes the following steps:
[0061] Step 1, preparation of polydimethylsiloxane slurry: 200 mL of chemical silver plating solution is added to 10 mL of polydimethylsiloxane prepolymer and reacted at room temperature for 40 minutes, nano silver conductive particles are generated in situ in the polydimethylsiloxane prepolymer through liquid phase reduction reaction, and then ultrasonically cleaned in an ultrasonic cleaner for 60 minutes so that the nano silver conductive particles are evenly dispersed in the polydimethylsiloxane prepolymer to obtain polydimethylsiloxane prepolymer containing in situ nano silver conductive particles; then 20 g of conductive graphite powder with a particle size of 5 to 10 μm is added to the polydimethylsiloxane prepolymer containing the nano silver conductive particles as micron conductive particles, and ultrasonically dispersed in an ultrasonic cleaner for 120 minutes so that the conductive graphite powder is evenly dispersed in the polydimethylsiloxane prepolymer to obtain a polymer conductive slurry.
[0062] The preparation process of the chemical silver plating solution includes the following steps: dissolving 20g of silver nitrate into 1L of deionized water, then slowly dropping ammonia water, and stopping dropping ammonia water when the solution changes from clear to turbid and then from turbid to colorless and transparent to obtain a silver ammonia solution; then adding 20g of glucose and mixing and stirring at room temperature for 60min to obtain a chemical silver plating solution.
[0063] Step 2: Soft etching of polydimethylsiloxane core mold: Add 1 mL of curing agent to the polydimethylsiloxane prepolymer matrix containing added micron conductive graphite powder, and then pour it onto a silicon template with a micro gear shape after mechanical stirring, and then place it in an oven at 100°C for curing for 60 minutes, and finally demold to obtain a polydimethylsiloxane core mold with a micro gear structure. Among them, the polydimethylsiloxane prepolymer matrix containing added micron conductive graphite powder is the polymer conductive slurry.
[0064] Step 3: Electroforming of micro gears: The polydimethylsiloxane core mold is used as the cathode and immersed in the nickel / alumina composite electroforming liquid. The pure nickel sheet is used as the anode and the electrochemical workstation is used for electroplating at 80°C. The current density used for electroplating is 3A / dm 2 The electrodeposition method is pulse electrodeposition, and the electrodeposition time is 15 hours. After the core model cavity is filled with casting, the electrodeposition is stopped to obtain a nanocrystalline nickel / aluminum oxide composite gear thin-walled part.
[0065] The components of the nickel / alumina composite electroforming solution include: 400 g / L nickel sulfate, 60 g / L boric acid, 40 g / L nickel chloride, 2 g / L sodium dodecyl sulfate, 18 g / L saccharin, 5 g / L glucose, and 20 g / L alumina powder with an average particle size of 0.3 μm. The pH value of the nickel / alumina composite electroforming solution is adjusted to 4 using a dilute sulfuric acid solution to improve the stability of the solution.
[0066] Step 4, demoulding and post-processing: The nanocrystalline nickel / alumina composite gear thin-walled part is removed from the core model cavity by manual demoulding, cleaned with anhydrous ethanol, and then placed in a muffle furnace for heat treatment at 300°C for 60 minutes, and finally surface polished to improve the meshing accuracy and surface quality of the gear. The polydimethylsiloxane core mold after demoulding is ultrasonically cleaned in deionized water for reuse.
[0067] Figure 3 The morphology of the nanocrystalline nickel / aluminum oxide composite gear with a tooth width of 200 μm prepared according to Example 2 is shown in FIG. Figure 3 It can be seen that the nanocrystalline nickel / aluminum oxide composite gear structure prepared in this embodiment is complete and has no defects, and completely replicates the microstructure of the original template. Therefore, the composite micro-gear prepared in the embodiment of the present disclosure has excellent replication forming accuracy.
[0068] Example 3
[0069] The nanocrystalline special-shaped thin-walled parts prepared in this embodiment are copper-nickel alloy thin-walled parts with grid line patterns for photovoltaic use. The polymer prepolymer used is polydimethylsiloxane prepolymer, and the metal ion solution is a chemical nickel plating solution. The added micron conductive particles are nickel powder. The original template is a stainless steel template surface with a grid line pattern, and the electroforming liquid is a copper-nickel alloy electroforming liquid. The specific preparation process includes the following steps:
[0070] Step 1, preparation of polydimethylsiloxane slurry: adding 100 mL of chemical nickel plating solution to 50 mL of polydimethylsiloxane prepolymer and reacting at room temperature for 40 minutes, in situ generating nano nickel conductive particles in the polydimethylsiloxane prepolymer through liquid phase reduction reaction, and then ultrasonically cleaning for 200 minutes in an ultrasonic cleaner so that the nano nickel conductive particles are evenly dispersed in the polydimethylsiloxane prepolymer to obtain polydimethylsiloxane prepolymer containing nano nickel conductive particles; then adding 120 g of nickel powder with a particle size of 1 to 3 μm to the polydimethylsiloxane prepolymer containing nano nickel conductive particles, ultrasonically dispersing for 150 minutes in an ultrasonic cleaner so that the nickel powder is evenly dispersed in the polydimethylsiloxane prepolymer matrix to obtain a polymer conductive slurry.
[0071] The chemical nickel plating solution contains the following components: 60 g / L nickel chloride, 30 g / L sodium citrate, 15 g / L sodium hypophosphite, and 15 g / L sodium acetate. The pH value of the chemical nickel plating solution is adjusted to 5.0 or other appropriate values by using a dilute hydrochloric acid solution to improve the solution stability.
[0072] Step 2: Soft etching of polydimethylsiloxane core mold: Add 5 mL of curing agent to the polydimethylsiloxane prepolymer matrix containing added micron nickel powder, and then pour it onto the surface of the stainless steel template with a grid line pattern after mechanical stirring, and then place it in an oven at 120°C for curing for 30 minutes, and finally demold to obtain a polydimethylsiloxane core mold with a grid line pattern. The polydimethylsiloxane prepolymer matrix containing added micron nickel powder is the polymer conductive paste.
[0073] Step 3: Electroforming of micro gears: The polydimethylsiloxane core mold is used as the cathode and immersed in the copper-nickel alloy electroforming liquid. The copper sheet and nickel sheet are used as the anode. Electrodeposition is performed at 50°C. The current density used for electrodeposition is 1A / dm 2 The electrodeposition method is pulse electrodeposition, and the electrodeposition time is 10 hours. After the core mold cavity is filled, the electrodeposition is stopped to obtain a nanocrystalline copper-nickel alloy grid line thin-walled part. Among them, the area ratio of the copper sheet and the nickel sheet as the anode can be 3:1, or other ratios, which are determined according to actual needs.
[0074] The copper-nickel alloy electroforming solution contains the following components: 270 g / L copper sulfate, 100 g / L nickel sulfate, 50 g / L sodium chloride, 30 g / L boric acid, 10 g / L saccharin and 1 g / L sodium dodecyl sulfate.
[0075] Step 4, demoulding and post-processing: Use manual demoulding to remove the nanocrystalline copper-nickel alloy grid line thin-walled parts from the core mold cavity, clean them with anhydrous ethanol, and then polish the surface to improve the grid line surface quality, so as to obtain photovoltaic grid line pattern thin-walled parts. After demoulding, the polydimethylsiloxane core mold is ultrasonically cleaned in deionized water for reuse.
[0076] Figure 4 The morphology of the nanocrystalline copper-nickel alloy gate line thin-walled member with a line width of 20 μm prepared in Example 3 is shown in FIG. Figure 4 It can be seen that the nanocrystalline copper-nickel alloy grid line thin-walled member prepared in this embodiment has a complete structure without defects and completely replicates the microstructure of the original template. Therefore, the alloy micro-pattern prepared in this embodiment has excellent replication forming accuracy.
[0077] Comparative Example
[0078] The preparation process mainly includes the following steps:
[0079] Step 1: Add 1 mL of curing agent to 10 mL of polydimethylsiloxane prepolymer, stir it mechanically to make it uniform, and then pour it onto a silicon template with a micro-gear shape. Then place it in an oven and cure it at 100°C for 60 minutes. Finally, demold it to obtain a polydimethylsiloxane core mold with a micro-gear structure.
[0080] Step 2: Use the polydimethylsiloxane core mold as the cathode and immerse it in the nickel sulfate electroforming solution. Use the pure nickel sheet as the anode and conduct the electrochemical workstation at 80°C with a current density of 3A / dm 2 Pulse electrodeposition.
[0081] In the above method, on the surface of the polymer core mold without conductive particles, due to the poor conductivity of the polymer, nickel ions cannot nucleate and grow on the surface of the core mold during the electrodeposition process, and ultimately no electroplating layer is generated on the surface of the core mold, and nanocrystalline special-shaped thin-walled parts cannot be generated.
[0082] In summary, the technical solution in the embodiment of the present disclosure, the uniform distribution of in-situ nano-conductive particles and external micron-conductive particles generated by mixing a polymer prepolymer with a metal ion solution can improve the uniformity of the distribution of electric lines during the electroforming process, which is beneficial to improving the forming accuracy. Soft etching can accurately replicate the shape of the original template, and the elastic polymer core mold can reduce the damage to the microstructure during the demolding process, thereby improving the forming accuracy. The elastic polymer core mold can release residual stress during the deposition process, avoid deformation and defects caused by stress concentration, and improve the service performance of the prepared nanocrystalline special-shaped thin-walled parts. The core mold is prepared by soft etching technology, without the need for expensive lithography equipment and complex processes, reducing the cost of core mold preparation. By using in-situ self-generation and external conductive particles, the traditional high-cost conductive materials are partially replaced, further reducing costs and increasing the service life of the core mold.
[0083] In the embodiment of the present disclosure, a nanocrystalline shaped thin-walled part is also provided, and the nanocrystalline shaped thin-walled part can be prepared according to the forming method of step S110 to step S140. The method of realizing the precision forming of nanocrystalline shaped thin-walled parts by soft etching combined with micro-electroforming reduces the core mold preparation cost and forming cycle, and improves the forming accuracy and service performance of the product.
[0084] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0085] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
[0086] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for forming a nanocrystalline special-shaped thin-walled part, characterized in that: include: The polymer prepolymer is mixed with a metal ion solution, and the metal ions are used to generate nano-conductive particles in the polymer prepolymer in situ through a liquid phase reaction, and micron-sized conductive particles are added to the polymer prepolymer containing the nano-conductive particles, and ultrasonically dispersed to obtain a polymer conductive slurry; Adding a curing agent to the polymer conductive slurry, stirring evenly and then pouring it onto the surface of the original template, and demolding after curing and forming to obtain a polymer core mold with the original template structure; The polymer core mold is immersed in an electroforming liquid as a cathode, and metal ions in the electroforming liquid are reduced to metal atoms by electrodeposition, and deposited in the core mold cavity until the core mold cavity is filled; The nanocrystalline special-shaped thin-walled part is demoulded from the core mold cavity to obtain the nanocrystalline special-shaped thin-walled part.
2. The forming method of nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The polymer prepolymer is polydimethylsiloxane or epoxy resin.
3. The forming method of nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The weight ratio of the metal ion solution to the polymer prepolymer is 2 to 3:
1.
4. The forming method of nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The micron conductive particles are metal powder or carbon-based conductive material, the metal powder is silver powder, copper powder or nickel powder, and the carbon-based conductive material is graphene, carbon nanotube or graphite.
5. The forming method of nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The weight ratio of the micron conductive particles to the polymer prepolymer is 2 to 5:
1.
6. The forming method of nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The weight ratio of the polymer conductive paste to the curing agent is 1 to 10:
1.
7. The method for forming a nanocrystalline special-shaped thin-walled part according to claim 1, characterized in that: The process parameters of the electrodeposition include one or more of current density, temperature and time, wherein the current density is 1 to 20 A / dm 2 The temperature is 30-80° C., and the time is determined according to the thickness of the nanocrystalline special-shaped thin-walled part.
8. The method for forming nanocrystalline special-shaped thin-walled parts according to claim 1, characterized in that: The electroforming liquid is a single metal electroforming liquid, an alloy electroforming liquid or a composite electroforming liquid.
9. The method for forming a nanocrystalline special-shaped thin-walled part according to claim 1, characterized in that: After demolding the nanocrystalline special-shaped thin-walled part from the core mold cavity, the method further comprises: The taken-out nanocrystalline special-shaped thin-walled parts are post-processed, and the post-processing includes one or more of ultrasonic cleaning, heat treatment and surface polishing.
10. A nanocrystalline special-shaped thin-walled part, characterized in that: The nanocrystalline special-shaped thin-walled part is prepared according to the forming method of the nanocrystalline special-shaped thin-walled part according to any one of claims 1-9.
Citation Information
Patent Citations
Metallic structures with variable properties
CN101903566A
Method and device for processing three-dimensional conductive microstructure
CN107839220A
Micro-electroforming method for imprint metal template based on multi-layer structure silicone rubber core mold
CN115821337A
Micro-electroforming method based on rigid clamp assisted conductive polymer core mold
CN116752200A
Polymer core mold micro-electroforming method based on in-situ synthesis conductive particles
CN116837428A
Cited By
Electroforming device and electroforming processing method
CN121321116A